Prospek Pengembangan Usahatani Tomat di Lahan Joni Roma Farm Desa Nita Kecamatan Nita Kabupaten Sikka - Yohanes Irfon Hendrian; Sarlina Noni (Jurnal Ilmiah Wahana Pendidikan, 2022)
Market demand for tomato commodities from year to year is increasing however, until now there are still many obstacles experienced by tomato farmers, ranging from problems of applying proper cultivation techniques, pest and disease problems to tomato crops, to problems marketing crops. This research aims to find out the Prospects for Tomato Farming Development in Joni Roma Farm Village Nita District Nita District Sikka Regency. As for the results of the research obtained that: the prospects of developing tomato farming business in Joni Roma Farm Land Nita Village Nita District Nita Sikka Regency, namely 1).increase market demand by utilizing, land area and supporting land in tomato cultivation, 2). utilizing technology and agroclimat land to improve product quality, 3) increase profits by increasing production through the utilization of labor and groups